Straddling (In)Visibility: Representations of Bisexual Women in Twenty-First Century Popular Culture - Cocarla, Sasha (Université d'Ottawa / University of Ottawa, 2016)
Throughout the first decade of the 2000s, LGBTQ+ visibility has steadily increased in North American popular culture, allowing for not only more LGBTQ+ characters/figures to surface, but also establishing more diverse and nuanced representations and storylines. Bisexuality, while being part of the increasingly popular phrase of inclusivity (LGBTQ+), however, is one sexuality that not only continues to be overlooked within popular culture but that also continues to be represented in limited ways. In this doctoral thesis I examine how bisexual women are represented within mainstream popular culture, in particular on American television, focusing on two, popular programs (The L Word and the Shot At Love series). These texts have been chosen for popularity and visibility in mainstream media and culture, as well as for how bisexual women are unprecedentedly made central to many of the storylines (The L Word) and the series as a whole (Shot At Love). This analysis provides not only a detailed historical account of bisexual visibility but also discusses bisexuality thematically, highlighting commonalities across bisexual representations as well as shared themes between and with other identities. By examining key examples of bisexuality in popular culture from the first decade of the twenty-first century, my research investigates how representations of bisexuality are often portrayed in conversation with hegemonic understandings of gender and sexuality, specifically highlighting the mainstream "gay rights" movement's narrative of "normality" and "just like you" politics. Finally, it is in recognizing how representations of bisexuality are framed by specific reoccurring themes/tropes, as well as how these themes/tropes work together within larger social, cultural, and political climates, that it becomes possible to challenge existing gender and sexuality norms and ideals and create a more nuanced and complex understanding of bisexuality.
Keywords: Bisexuality; Popular Culture; Queer Theory; Representations; Television; LGBTQ